COMBATING ILLEGAL DRUG TRAFFICKING - Musaev Djamaliddin Kamalovich (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract. This article is devoted to the problem of drug addiction spreading among a part of the youth, as well as the fight against drug addiction. It examines the current issues in the country. The experience of foreign countries in this field is considered, especially in prevention and deterrence of drug dependence among certain population groups. Measures are proposed that could potentially limit this antisocial phenomenon.